Digital subtraction angiography-guided peripheral nerve stimulation via the foramen rotundum for refractory trigeminal postherpetic neuralgia: a case report and literature review - Xu, Qingbang; Zhou, Fangyuan; Yang, Dong (Frontiers in Neurology, 2024)
Postherpetic neuralgia (PHN) is a debilitating complication of varicella-zoster virus infection. This case report presents a novel approach to treating refractory trigeminal maxillary postherpetic neuralgia using digital subtraction angiography (DSA)-guided peripheral nerve stimulation via the foramen rotundum. A 72-year-old female with severe, treatment-resistant pain underwent this intervention. The results demonstrated the disappearance of tactile allodynia, a significant reduction in oral analgesic requirements, and no observed complications or side effects during a 3-year follow-up period. This case highlights the potential effectiveness of DSA-guided peripheral nerve stimulation using a new dorsal root ganglion (DRG) stimulator as an alternative therapy for refractory trigeminal postherpetic neuralgia (TPHN).